GOOD CORPORATE GOVERNANCE (GCG) AND CORPORATE SOCIAL RESPONSIBILITY IMPACT ON FINANCIAL PERFORMANCE: MODERATING ROLE OF EARNINGS MANAGEMENT - Aurelia, Sharlyn; Yanti, Yanti (International Journal of Application on Economics and Business, 2025)
This research investigates the relationship between good corporate governance (GCG) and corporate social responsibility (CSR), along with the moderating role of earnings management. Focusing on companies in the consumer cyclicals sector listed on the Indonesia Stock Exchange from 2021-2023, the study employs a descriptive design and purposive sampling, resulting in 216 observations from 72 companies. Data were analyzed using multiple regression techniques. The findings indicate that good corporate governance, as represented by institutional ownership, managerial ownership, the audit committee, and independent commissioners, does not have a significant impact on financial performance. Furthermore, corporate social responsibility is found to positively and significantly influence financial performance. Notably, earnings management does not significantly moderate the effect of good corporate governance on financial performance, and it exhibits a negative moderating effect on the relationship between CSR and financial performance. These insights deepen our understanding of the dynamics affecting financial performance in the Indonesian consumer cyclicals sector, highlighting the critical importance of strategic financial management in enhancing corporate outcomes.